Inmunohistochemical identification of angiotensin II antigen receptors in umbilical artery of alpaca (Vicugna pacos) - Ayala C., Emanuel (2020)
The aim of this study was to identify the angiotensin II receptor antigens in the umbilical artery of the alpaca (Vicugna pacos). Six gravid uteri of alpacas from community farms located at 4000 m above the sea level in Cusco, Peru were used. The gestation time was estimated by the biparietal diameter of the foetus. Histological sections of 5 µm thickness were obtained from each umbilical artery. The Avidin-Biotin-peroxidase immunohistochemistry (IHQ) technique was applied, using IHQ reagents and polyclonal anti-Angiotensin II antibodies. The slides were analysed with a Leica DM750 binocular microscope with digital camera attached and LAS 4.7 Leica Macrosystems software. The intensity of marking was classified qualitatively (0: negative; 1: weak; 2: moderate; 3: strong labelling). For the positive control, ovine umbilical artery samples were used. The angiotensin II receptor antigens were in the smooth muscle cells of the umbilical arteries in the various gestation times. The antigens showed a strong labelling intensity, showing that angiotensin exerts its biological activity of vasoconstriction in the smooth muscle cells of the blood vessel.